Assessment of Occupational Stress, Support Systems and Coping Strategies among APF Disaster Rescuers - Shrestha , Yogesh Man; Shrestha, Raju (Journal of APF Command and Staff College, 2025)
Occupational stress is a critical concern for disaster responders due to the high-risk and unpredictable nature of their duties. This study investigates occupational stress, support systems, and coping strategies among Armed Police Force (APF), Nepal disaster rescuers, with a focus on identifying key stressors and proposing interventions. A structured questionnaire was administered to 89 APF personnel selected randomly across multiple disaster response units. Descriptive and inferential statistical analyses were used to assess the impact of demographic factors on various stress related constructs and coping and support systems. Findings indicate that while institutional support and coping strategies effectively mitigate stress, longer service duration and frequent deployments lead to cumulative psychological strain. The study highlights the need for continuous monitoring, structured mental health interventions, and specialized training to address the long-term effects of occupational stress. Beyond traditional stress management programs, the study stresses a need for innovative interventions, such as technology-based solutions.